If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1b + 8 = 5b + 4 Reorder the terms: 8 + -1b + 2x = 5b + 4 Reorder the terms: 8 + -1b + 2x = 4 + 5b Solving 8 + -1b + 2x = 4 + 5b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-5b' to each side of the equation. 8 + -1b + -5b + 2x = 4 + 5b + -5b Combine like terms: -1b + -5b = -6b 8 + -6b + 2x = 4 + 5b + -5b Combine like terms: 5b + -5b = 0 8 + -6b + 2x = 4 + 0 8 + -6b + 2x = 4 Add '-8' to each side of the equation. 8 + -6b + -8 + 2x = 4 + -8 Reorder the terms: 8 + -8 + -6b + 2x = 4 + -8 Combine like terms: 8 + -8 = 0 0 + -6b + 2x = 4 + -8 -6b + 2x = 4 + -8 Combine like terms: 4 + -8 = -4 -6b + 2x = -4 Add '-2x' to each side of the equation. -6b + 2x + -2x = -4 + -2x Combine like terms: 2x + -2x = 0 -6b + 0 = -4 + -2x -6b = -4 + -2x Divide each side by '-6'. b = 0.6666666667 + 0.3333333333x Simplifying b = 0.6666666667 + 0.3333333333x
| h(x)=2x+4 | | 2532500/x/1277.59=27.68 | | z+2(4+z)=3z+8 | | (3x^4y^3)(9x^2y^6)= | | 10y=2x+5 | | (3-2g)(7-g)=0 | | 2(R+10)=68 | | 15x^3y^11= | | ax+3b=9b | | 0=k-4+4 | | -750c^5+162c^2=0 | | 5x=3x-17 | | 2+6x+2=4 | | (3xy^10)(5x^2y)= | | x+3=8x-4 | | w^2-33w=0 | | m/n-7 | | 6-(2x-4)+x=3 | | k^2-15k=0 | | 5x+3-8=12 | | 7(1+x)=-147 | | 20m^2-9m=0 | | 7(1+x)=-146 | | 6(6-8x)=4(6-10x) | | j^2-28j=0 | | -3x+7+7x+7=15 | | -4(n+4)=-24 | | 2533000/x/1277.59=27.68 | | f(-2)=3(-2)-9 | | 5*5*5*5=70 | | 17n^2-29n=0 | | -9x-7-4x-6=15 |